2000
DOI: 10.1177/002221940003300302
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Between Difficult-to-Remediate and Readily Remediated Poor Readers

Abstract: In this article we discuss research bearing on the traditional use of the IQ-achievement discrepancy to define specific reading disability. We initially review the evidence presented by Rutter and Yule (1975) in support of this practice, and then discuss results from subsequent studies that have questioned the reliability of their findings. We also discuss results from more recent studies demonstrating that the IQ-achievement discrepancy does not reliably distinguish poor from normal readers, whereas language-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 326 publications
(129 citation statements)
references
References 26 publications
6
119
1
3
Order By: Relevance
“…Findings from a variety of studies indicate that both dyslexic and garden-variety disabled readers demonstrate phonological processing deficits that are not related to IQ test scores, but are common to both groups of readers (Gresham & Vellutino, 2010;Siegel, 1998;Stanovich, 1988;Stanovich & Siegel, 1994;Vellutino et al, 1996). Furthermore, evidence indicated the IQ-discrepancy model did not differentiate between children who could be easily remediated versus those children who were more difficult to remediate (Gresham & Vellutino, 2010;Vellutino et al, 1996;Vellutino et al, 2000;Vellutino et al, 2006). Although the IQ-discrepancy model has not disappeared from the educational landscape and continues to be used in school environments, renunciation of this model by the research community demonstrated a significant change in perspective regarding the identification of children with reading disabilities and encouraged the development of improved methods for identification purposes.…”
Section: Iq-discrepancy Model As a Methods For The Identification Of Dmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings from a variety of studies indicate that both dyslexic and garden-variety disabled readers demonstrate phonological processing deficits that are not related to IQ test scores, but are common to both groups of readers (Gresham & Vellutino, 2010;Siegel, 1998;Stanovich, 1988;Stanovich & Siegel, 1994;Vellutino et al, 1996). Furthermore, evidence indicated the IQ-discrepancy model did not differentiate between children who could be easily remediated versus those children who were more difficult to remediate (Gresham & Vellutino, 2010;Vellutino et al, 1996;Vellutino et al, 2000;Vellutino et al, 2006). Although the IQ-discrepancy model has not disappeared from the educational landscape and continues to be used in school environments, renunciation of this model by the research community demonstrated a significant change in perspective regarding the identification of children with reading disabilities and encouraged the development of improved methods for identification purposes.…”
Section: Iq-discrepancy Model As a Methods For The Identification Of Dmentioning
confidence: 99%
“…This model required the demonstration of discrepant scores on IQ and achievement tests in order to diagnose a reading disability and presumed that discrepant readers identified as dyslexic differed significantly from their garden-variety counterparts who lacked discrepant scores due to low IQ scores and demonstrated weaknesses in both decoding and comprehension (Gough & Tunmer, 1986;Lyon, 1995). Application of the IQ-discrepancy model reflected the influence of studies conducted by Rutter and Yule during the 1970s (Fletcher et al, 1994;Gresham & Vellutino, 2010;Vellutino et al, 2000). Rutter and Yule (1975) identified two types of disabled readers:…”
Section: Defining Dyslexia Prior To 2002mentioning
confidence: 99%
See 3 more Smart Citations